2013
DOI: 10.1111/asj.12088
|View full text |Cite
|
Sign up to set email alerts
|

Effects of animal liver and bile extracts on biochemical values of rat ethanol‐induced fatty liver

Abstract: The purposes of this study were to assess the improvement of fatty liver induced by ethanol with animal liver and bile extracts. This research aimed to increase the economic values of animal liver and bile extracts and used these to reduce damage of ethanol-induced fatty liver. Extracts came from animal liver and bile, including pig bile powder, pig liver extract, a mixture of pig bile powder and pig liver extract, chicken bile powder, chicken liver extract, and a mixture of chicken bile powder and chicken liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…The majority of ALB is synthesized in the liver. Therefore, variation of serum TP or ALB concentrations can reflect liver health status (Wan et al, 2014). In the current study, a marked decrease of serum TP and ALB levels were observed in PCM-hepatotoxic rats compared with the normal control animals.…”
Section: Serum and Liver Biochemical Markerssupporting
confidence: 53%
“…The majority of ALB is synthesized in the liver. Therefore, variation of serum TP or ALB concentrations can reflect liver health status (Wan et al, 2014). In the current study, a marked decrease of serum TP and ALB levels were observed in PCM-hepatotoxic rats compared with the normal control animals.…”
Section: Serum and Liver Biochemical Markerssupporting
confidence: 53%
“…Recent findings suggest that the liver itself produces a secretome endowed with anti-inflammatory properties [22]. In this context, a supplement based on liver from healthy animals could be worthy of analysis [39], both as nutraceutical and substrate for studying hepatocyte biology. The aim of this work was the preliminary assessment of the in vitro bioactivity and safety of a freeze-dried liver preparation of porcine origin.…”
Section: Discussionmentioning
confidence: 99%